2004
DOI: 10.2460/ajvr.2004.65.1483
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the transmission of Mycobacterium bovis from deer to cattle through indirect contact

Abstract: Objective—To investigate the infection of calves with Mycobacterium bovis through oral exposure and transmission of M bovis from experimentally infected white-tailed deer to uninfected cattle through indirect contact. Animals—24 11-month-old, white-tailed deer and 28 6-month-old, crossbred calves. Procedure—In the oral exposure experiment, doses of 4.3 × 106 CFUs (high dose) or 5 × 103 CFUs (low dose) of M bovis were each administered orally to 4 calves; as positive controls, 2 calves recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 21 publications
1
69
1
1
Order By: Relevance
“…Likewise, direct transmission between wildlife and farmed animals has not been demonstrated yet under natural conditions. Nev-ertheless, it has been demonstrated that experimentally infected deer can transmit M. bovis to cattle through the sharing of feed (22).…”
mentioning
confidence: 99%
“…Likewise, direct transmission between wildlife and farmed animals has not been demonstrated yet under natural conditions. Nev-ertheless, it has been demonstrated that experimentally infected deer can transmit M. bovis to cattle through the sharing of feed (22).…”
mentioning
confidence: 99%
“…Bucks are more likely to be bTB-positive than does and should be included in any mitigation methods considered. For pathogens that can be transmitted between livestock and wildlife, the risk for transmission often increases near farms (Palmer et al 2004). Focusing on culling, vaccine deployment or other mitigation methods on farms may serve as a logistically and financially effective method to target deer that are at highest risk for transmission of pathogens between livestock.…”
Section: Disease Management Implicationsmentioning
confidence: 99%
“…Studies by Palmer et al (2004), suggest indirect contact resulting from shared feed is a likely mechanism for intraspecific transmission between deer and interspecific transmission between deer and cattle. Epidemiologic investigations of infected white-tailed deer in Michigan found supplemental feeding of deer likely contributes to infection in deer with subsequent spillover to cattle (Miller et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological and strain typing evidence suggests that infected WTD serve as a reservoir since interspecies transmission from deer to cattle occurs (21,25,29). In Minnesota, infected WTD have been found adjacent to infected cattle (http://www.bah.state.mn.us/tb/).…”
mentioning
confidence: 99%